Folding of the conserved domain but not of flanking regions in the integrin β(2) subunit requires association with the α subunit - Huang, Chichi (The National Academy of Sciences of the USA, 1997)
We have used immunoprecipitation with mAbs to probe folding during biosynthesis of the β(2) integrin subunit of lymphocyte function-associated antigen 1 (LFA-1; CD11a/CD18) before and after association with the α(L) subunit. An evolutionarily conserved region is present in the β(2) subunit between amino acid residues 102 and 344. mAbs to one subregion before the conserved region, and two subregions after the conserved domain, immunoprecipitated both the unassociated β′(2) precursor and mature α(L)/β(2) complex, suggesting portions of these subregions are folded before association with α(L). An activating mAb to the C-terminal cysteine-rich region, KIM127, preferentially bound to the unassociated β subunit, suggesting that it may bind to an epitope that is in an αβ interface in unactivated LFA-1. By contrast, mAbs to five different epitopes in the conserved region did not react with unassociated β′(2) precursor, suggesting that this region folds after α(L) association and is intimately associated with the α(L) subunit in the α(L)/β(2) complex. mAbs to two different epitopes that involve the border between the conserved region and the C-terminal segment, were fully or partially reactive with the β′(2) precursor, suggesting that this region is partially folded before association with α(L). The findings suggest that the conserved region is a distinct folding and hence structural unit, and is intimately associated with the α subunit.